Chaos-Driven Encryption: A New Frontier For IoT Image Security Using Multi-Linear Systems - S. N., Prajwalasimha; P., Ranjima; V., Vinitha; Kulkarni, Naveen; K., Deepthika (Journal of Information Systems Research and Practice, 2024)
In the context of an increasingly digital world, safeguarding sensitive visual information from unauthorized access is essential, particularly within resource-constrained Internet of Things (IoT) environments. This study introduces a novel image encryption method leveraging a Pseudo Hadamard Transformation (PHT), designed to provide a lightweight and efficient alternative to conventional pixel scrambling techniques. The proposed approach integrates chaos-based diffusion methods, which significantly enhance the encryption framework by effectively obscuring the correlation between the original image (plaintext) and the encrypted image (ciphertext). Through rigorous evaluations, the method demonstrates impressive statistical security metrics, achieving a Number of Pixels Change Rate (NPCR) of 99.6064 for the Lenna image, indicating a high degree of pixel alteration in response to single-pixel changes. Additionally, a Unified Average Changing Intensity (UACI) value of 33.4682 for the Lenna image highlights considerable intensity variations, further reinforcing the encryption's robustness. Compared to existing encryption techniques, the proposed method excels in both NPCR and UACI values, underscoring its superior performance and security capabilities. This hybrid encryption scheme, characterized by its efficient computational requirements and strong security features, is particularly well-suited for IoT applications, where maintaining a balance between data protection and resource limitations is paramount. The findings suggest that PHT, coupled with chaos-based diffusion, offers a promising solution for enhancing visual data security in modern digital environments.